2003
DOI: 10.1128/jcm.41.1.267-272.2003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Heteroresistance to Fluconazole among Clinical Isolates of Cryptococcus neoformans

Abstract: Strains of Cryptococcus neoformans expressing heteroresistance to fluconazole have been described previously. The present study was conducted to investigate the prevalence of heteroresistance among clinical isolates of C. neoformans and to characterize the heteroresistant phenotypes. A total of 107 clinical isolates of C. neoformans for which the MICs of fluconazole ranged from 0.25 to 32 g/ml were selected. The isolates were chosen to represent a broad geographic distribution. Of the 107 C. neoformans isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 26 publications
0
39
0
4
Order By: Relevance
“…Strikingly, the resistance is affected by temperature, as it is suppressed at 35°C and abolished at 40°C. A subsequent study examining 107 clinical isolates found fluconazole heteroresistance in 5 isolates and confirmed both that fluconazole resistance could be developed by selection of heteroresistant clones in the presence of fluconazole and that heteroresistance was suppressed at increased temperatures (236). Notably, separate from the phenomenon of heteroresistance, the patterns of mutation to fluconazole resistance in C. neoformans are complex.…”
Section: Resistance To Drugs Exerting Cell Membrane Stressmentioning
confidence: 91%
“…Strikingly, the resistance is affected by temperature, as it is suppressed at 35°C and abolished at 40°C. A subsequent study examining 107 clinical isolates found fluconazole heteroresistance in 5 isolates and confirmed both that fluconazole resistance could be developed by selection of heteroresistant clones in the presence of fluconazole and that heteroresistance was suppressed at increased temperatures (236). Notably, separate from the phenomenon of heteroresistance, the patterns of mutation to fluconazole resistance in C. neoformans are complex.…”
Section: Resistance To Drugs Exerting Cell Membrane Stressmentioning
confidence: 91%
“…This finding may explain clinical failure of antimicrobial treatment when the more susceptible strain has been picked for the antibiogram. We recently described the same phenomenon in other E. coli extraintestinal infections [43], and it has been reported for other microorganisms [44][45][46][47]. We, therefore, believe that several colonies of a single respiratory sample should be tested for antimicrobial susceptibility in case of GNB VAP.…”
Section: Discussionmentioning
confidence: 99%
“…The resistant subpopulations can adapt to increasing concentrations of the azoles in a stepwise manner; however, the original susceptibility is restored after passage in the absence of an antifungal. This mechanism of resistance has been observed among clinical isolates and is unrelated to prior drug exposure and unaffected by pH or osmolarity (387,639). Notably, resistance is affected by temperature, as heteroresistance phenotypes can be suppressed at 35°C and are abolished at 40°C (387,639).…”
Section: Cellular Stress Responsesmentioning
confidence: 99%
“…This mechanism of resistance has been observed among clinical isolates and is unrelated to prior drug exposure and unaffected by pH or osmolarity (387,639). Notably, resistance is affected by temperature, as heteroresistance phenotypes can be suppressed at 35°C and are abolished at 40°C (387,639). Most recently, a study analyzing 130 C. neoformans strains isolated from clinical and environmental sources before 1979, prior to azole use, and 16 fluconazole-resistant strains isolated from AIDS patients undergoing fluconazole therapy from 1990 to 2000 found that all the strains manifested heteroresistance, confirming that this phenomenon is universal and unrelated to prior drug exposure (537).…”
Section: Cellular Stress Responsesmentioning
confidence: 99%